Viscerosomatic, hepatosomatic indices and condition factor of Barbonymus and Osteochilus genus in the freshwater river of North Aceh, Indonesia - Putra Abdul Samad Agus; Junita Afrah; Ilman Navia Zidni (BIO Web of Conferences)
North Aceh is one of the regencies in the Aceh province that has extensive freshwater fisheries. Commonly freshwater species found in this area are Barbonymus and Osteochilus genus. This study was conducted to analyse the viscerosomatic, hepatosomatic index, and condition factor of these species. Specimens were caught using fishing nets, gill nets, and fish traps. The data collection took place in 10 villages, and sampling were collected from July to August 2024. The observed parameters during the study were the viscerosomatic index, hepatosomatic index, condition factor, and water quality parameters. All samples were measured for weight and length, and then dissected to measure the viscerosomatic and hepatosomatic indices. This study found 6 species of Barbonymus and 4 species of Osteochilus genus, totaling 123 and 96 specimens respectively. Length and weight of Barbonymus genus of six species were 10.20 – 15.50 cm and 14.47 – 51.83 g, respectively, while the Osteochilus genus showed a range of 12.70 – 17.30 cm and 22.99 - 70.21 g. The condition factor of the Barbonymus genus varied from 0.97 - 1.39, while in the Osteochilus genus was 1.10 – 1.36. The VSI of Barbonymus genus was 5.98 – 8.50%. whereas, the Osteochilus genus showed a range of 7.18 – 29.97%.